LEARNING STRATEGY FOR WRITING SHORT STORY WITH NUSANTARA VALUE BASED ON HYPNOTEACHING - Widyartono, Didin; Anggara, Rayhan Adi; Ivana, Laili (RETORIKA: Jurnal Bahasa, Sastra, dan Pengajarannya, 2025)
This study aims to analyze scientific articles on short story writing learning strategies to construct a learning strategy for writing short stories with archipelago values based on hypnoteaching. This research uses a systematic literature review method. Data and data sources, namely, articles sourced from the google scholar database. Data collection is done by browsing the google scholar data base. The data analysis technique uses descriptive analysis. The results showed that Nusantara values are relevant to be used as an approach in developing teaching materials for writing short stories. Then hypnoteaching as a strategy is proven to improve students' writing skills because students become the center of learning and are encouraged to explore and reflect on Nusantara values. The implication of this research finding can be used to develop a learning strategy for writing short stories with archipelago values based on hypnoteaching. The findings are relevant in supporting the vision of national education to create a generation that is creative, innovative, and culturally characterized.